Literature Review: The Effect of Lemongrass Extract to Reduce Neurological Diseases in The Elderly - Sudibia, Ni komang Mentary Putri (Jurnal Health Sains, 2025)
Neurology is a field of medicine that focuses on the human brain. However, the elderly experience a natural aging process that causes changes in the brain and nervous system, increasing the risk of developing neurological diseases. One of them is dementia or alzheimer's disease, Parkinson's disease, seizures, stroke, sleep disorders, and others. The purpose of this study was to analyze the effect of lemongrass extract on reducing neurological diseases in the elderly. The research method was a systematic literature review on theses, articles, and books published in the range of 2018-2024. Data were collected from three databases (Google scholar, pubmed, and garuda portal) using the keywords "Lemongrass extract" and "Neurological diseases". The results obtained in this study indicate that lemongrass extract has an effect on reducing neurological diseases in the elderly, which can reduce dementia or alzheimer's disease, parkinson's disease, seizures, stroke, sleep disorders. So by using or consuming lemongrass drinks, lemongrass aromatherapy, lemongrass oil for foot massage, lemongrass decoction compresses, lemongrass extract drugs, lemongrass water foot soaks, lemongrass water for bathing can reduce neurological diseases in the elderly.